Development of Methane and Nitrous Oxide Emission Factors for the Biomass Fired Circulating Fluidized Bed Combustion Power Plant - Chang-Sang Cho; Jae-Hwan Sa; Ki-Kyo Lim; Tae-Mi Youk; Seung-Jin Kim; Seul-Ki Lee; Eui-Chan Jeon (The Scientific World Journal)
This study makes use of this distinction to analyze the exhaust gas concentration and fuel of the circulating fluidized bed (CFB) boiler that mainly uses wood biomass, and to develop the emission factors of Methane (CH4), Nitrous oxide (N2O). The fuels used as energy sources in the subject working sites are Wood Chip Fuel (WCF), RDF and Refused Plastic Fuel (RPF) of which heating values are 11.9 TJ/Gg, 17.1 TJ/Gg, and 31.2 TJ/Gg, respectively. The average concentrations of CH4 and N2O were measured to be 2.78 ppm and 7.68 ppm, respectively. The analyzed values and data collected from the field survey were used to calculate the emission factor of CH4 and N2O exhausted from the CFB boiler. As a result, the emission factors of CH4 and N2O are 1.4 kg/TJ (0.9–1.9 kg/TJ) and 4.0 kg/TJ (2.9–5.3 kg/TJ) within a 95% confidence interval. Biomass combined with the combustion technology for the CFB boiler proved to be more effective in reducing the N2O emission, compared to the emission factor of the CFB boiler using fossil fuel.